Efficacy and safety of Lenvatinib-based combination therapies for patients with unresectable hepatocellular carcinoma: a single center retrospective study - Huang, Jian; Wang, Zhen-Guang; Tao, Qi-Fei; Yang, Yun; Yuan, Sheng-Xian; Gu, Fang-Ming; Liu, Hui; Pan, Ze-Ya; Jiang, Bei-Ge; Lau, Wan Yee; Zhou, Wei-Ping (Frontiers in Immunology, 2023)
Background Reports on Lenvatinib-based therapies show promising treatment outcomes for patients with unresectable hepatocellular carcinoma (uHCC). However, the effect and safety of Lenvatinib-based therapies still need to be further studies. Methods This was a retrospective, single-center study on the safety and treatment efficacy of Lenvatinib-based combination therapies for uHCC Patients. The primary endpoints were progression-free survival (PFS) and overall survival (OS). The secondary endpoints were progressive disease (PD), stable disease (SD), partial response (PR), and complete response (CR). Results Of 91 patients, there were 16 females and 75 males with uHCC who received systemic therapies based on Lenvatinib in our center. Forty-six patients (50.5%) received Lenvatinib combined with PD-1 antibody treatment. All these patients also received local therapy with the exception of 2 patients. The remaining 36 patinets received Lenvatinib combined with transcatheter arterial chemoembolization (TACE), 1 patient treated Lenvatinib combined with radiotherapy, 8 patients received Lenvatinib alone. At a median treatment time of 8 months, the objective response rate (ORR) of the entire cohort was 58.2% (53 patients), including 7 patients with CR and 46 patients with PR. 21 patients (23.1%) had SD. The disease control rate (DCR) of all patients was 81.3% (74 patients). However, 17 patients (18.7%) developed PD. The 1- and 2-year cumulative OS rates for the entire cohort were 66.8% and 39.3%, while the corresponding PFS rates were 38.0% and 17.1%, respectively. Univariate and multivariate Cox regression analysis revealed multiple tumor sites to be an independent OS risk factor for uHCC patients (HR=2.204, 95% CI=1.104-4.399, P=0.025). The most frequently reported adverse events in all patients were AST elevation (51.6%), followed by hypertension (33.0%), ALT elevation (26.4%), and decreased appetite (25.3%). After a combination treatment of Lenvatinib-based therapies, 15 patients met the criteria for salvage liver resection and underwent down-staging hepatectomy with a curative intent. The combination of PD-1 treatment was not very effective in improving the prognosis of uHCC patients treated with Lenvatinib combined with TACE. Conclusion Our study demonstrated that a proportive of patients benefited from Lenvatinib-based combination therapies with manageable safety profiles, allowing these patients to undergo downstaging surgery with curative intent.